Dietary Bacillus NP5 supplement impacts on growth, nutrient digestibility, immune response, and resistance to Aeromonas hydrophila infection of African catfish, Clarias gariepinus - Achmad Noerkhaerin Putra; Mustahal Mustahal; Mas Bayu Syamsunarno; Dodi Hermawan; Devia Gusnur Fatimah; Pramodita Balita Putri; Sevia Sevia; Rina Isnaeni; Muhamad Herjayanto (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Putra AN, Mustahal, Syamsunarno MB, Hermawan D, Fatimah DG, Putri PB, Sevia, Isnaini R, Herjayanto M. 2021. Dietary Bacillus NP5 supplement impacts on growth, nutrient digestibility, immune response, and resistance to Aeromonas hydrophila infection of African Catfish, Clarias gariepinus. Biodiversitas 22: 253-261. This study aims to investigate the effects of Bacillus NP5 supplementation as a probiotic on growth, immune response, and resistance of African catfish to Aeromonas hydrophila infection. Catfish with an initial weight of 6.8 ± 0.1 g were fed with different doses of Bacillus NP5 (0%, 1.1%, 1.2% B, 1.3%, and 1.4%) with three replications and reared for 60 days. The first 45 days were used to observed growth performance, and the last 15 days were used to perform challenge tests against A. hydrophila infection. The results showed that the treatment of 1.2% Bacillus NP5 results in the highest specific growth rate (2.55±0.28 day-1) and increased protein and lipid digestibility significantly (P<0.05). Treatment of 1.1-1.3% Bacillus NP5 increase amylase and lipase activity that significantly higher than 0% Bacillus NP5 treatment. Supplementation of Bacillus NP5 significantly increased the leukocyte, phagocytic index, and survival rate in African catfish after A. hydrophila infection. Therefore, the supplementation of 1.2% Bacillus NP5 in the feed increased the growth, immune response, and African catfish resistance to the infection.